2008
DOI: 10.1001/archpsyc.65.7.841
|View full text |Cite
|
Sign up to set email alerts
|

The Incentive Salience of Alcohol

Abstract: Context The gene that codes for cannabinoid receptor 1 (CNR1) represents an important target for investigations designed to elucidate individual differences in the etiology of alcohol dependence. Objective To achieve a better understanding of the role of the CNR1 gene in the etiology and treatment of alcohol dependence. Design The present investigation spans multiple levels of analysis, including receptor binding in postmortem brain tissue, neuroimaging, human laboratory models, and analyses of treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(52 citation statements)
references
References 49 publications
2
50
0
Order By: Relevance
“…Accordingly, individuals also differ considerably in their susceptibility to mesolimbic sensitization, even when exposed to the same drugs and doses (Becker, Perry, & Westenbroek, 2012; Robinson & Berridge, 2008). Genetic factors are important determinants of susceptibility to sensitization in rodents, and genes also contribute strongly to addiction vulnerability in humans (Franklin et al, 2011; Hoft, Stitzel, Hutchison, & Ehringer, 2011; Hutchison et al, 2008; Moeller et al, 2013). Other determinants of sensitization vulnerability include gender and the presence of sex hormones, and whether the individual has had major stresses in life before taking drugs (Becker, Perry, & Westenbroek, 2012; T.…”
Section: Addiction Distorts ‘Wanting’ Versus ‘Liking’mentioning
confidence: 99%
“…Accordingly, individuals also differ considerably in their susceptibility to mesolimbic sensitization, even when exposed to the same drugs and doses (Becker, Perry, & Westenbroek, 2012; Robinson & Berridge, 2008). Genetic factors are important determinants of susceptibility to sensitization in rodents, and genes also contribute strongly to addiction vulnerability in humans (Franklin et al, 2011; Hoft, Stitzel, Hutchison, & Ehringer, 2011; Hutchison et al, 2008; Moeller et al, 2013). Other determinants of sensitization vulnerability include gender and the presence of sex hormones, and whether the individual has had major stresses in life before taking drugs (Becker, Perry, & Westenbroek, 2012; T.…”
Section: Addiction Distorts ‘Wanting’ Versus ‘Liking’mentioning
confidence: 99%
“…Candidate gene studies are very often undertaken from this perspective. For example, a recent study suggested that the effects of the cannabinoid 1 receptor gene (CNR1) on the risk for an alcohol use disorder is mediated by the effect of CNR1 on both the effect of alcohol on the brain and sensitivity to the rewarding effects of alcohol [23]. Similarly, others have shown that the FTO gene appears to influence obesity partially through its effects on energy intake and reduced perceptions of satiety [1].…”
Section: Indirect Influences Of Genomics On Health Behaviormentioning
confidence: 99%
“…This SNP located in exon three encodes an A–G substitution resulting in an alternative splice variant [Zhang et al, 2004]. The rs2023239 G allele has been demonstrated to be associated with greater CB1 expression in postmortem prefrontal cortex [Hutchison et al, 2008] and greater withdrawal and craving in recently abstinent cannabis users [Haughey et al, 2008]. Variation in rs2023239 also appears to influence brain response to cannabis cues with greater activation in reward circuitry including the orbitofrontal cortex, anterior cingulate gyrus, and nucleus accumbens [Filbey et al, 2010].…”
Section: Discussionmentioning
confidence: 99%